Application of Procedural Justice vis a vis Substantive Justice in Law Enforcement - Efendi, Jonaedi (Universitas Brawijaya, 2024)
This study examines the application of procedural and substantive justice in law enforcement. The research method employed in this article is a mixed-method approach, encompassing normative and sociological legal research. Normative legal research uses conceptual and case approaches, while sociological legal research adopts a socio-legal approach, analysing law enforcement from the perspective of legal culture. The discussion reveals that the application of procedural justice, in contrast to substantive justice in law enforcement, often cannot run simultaneously. In certain circumstances, procedural justice takes precedence, while in others, substantive justice is prioritised. Procedural justice is closely associated with the propriety and transparency of the decision-making process, whereas substantive justice emphasises elements within the law, particularly notions of ‘truth’ and ‘guilt’. However, both forms of justice must remain grounded in existing legal norms. Based on the findings of this study, it can be concluded that a discourse on the application of procedural justice versus substantive justice in law enforcement has emerged. This discourse is categorised into three stages: the investigation stage, the prosecution stage and the decision stage.